Consensus Statement on Advancing Research in Emergency Department Operations and Its Impact on Patient Care. (25th May 2015) - Yiadom, Maame Yaa A. B.; Ward, Michael J.; Chang, Anna Marie; Pines, Jesse M.; Jouriles, Nick; Yealy, Donald M.; the Emergency Department Operations Study Group; Newgard, Craig
Abstract The consensus conference on "Advancing Research in Emergency Department (ED) Operations and Its Impact on Patient Care, " hosted by The ED Operations Study Group (EDOSG), convened to craft a framework for future investigations in this important but understudied area. The EDOSG is a research consortium dedicated to promoting evidence‐based clinical practice in emergency medicine. The consensus process format was a modified version of the NIH Model for Consensus Conference Development. Recommendations provide an action plan for how to improve ED operations study design, create a facilitating research environment, identify data measures of value for process and outcomes research, and disseminate new knowledge in this area. Specifically, we call for eight key initiatives: 1) the development of universal measures for ED patient care processes; 2) attention to patient outcomes, in addition to process efficiency and best practice compliance; 3) the promotion of multisite clinical operations studies to create more generalizable knowledge; 4) encouraging the use of mixed methods to understand the social community and human behavior factors that influence ED operations; 5) the creation of robust ED operations research registries to drive stronger evidence‐based research; 6) prioritizing key clinical questions with the input of patients, clinicians, medical leadership, emergency medicine organizations, payers, and other government stakeholders; 7) more consistently defining the functional components of the ED care system, including observation units, fast tracks, waiting rooms, laboratories, and radiology subunits; and 8) maximizing multidisciplinary knowledge dissemination via emergency medicine, public health, general medicine, operations research, and nontraditional publications.